2020
DOI: 10.1002/pd.5725
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes associated with chorioamnion membrane separation severity following fetoscopic laser surgery for twin‐twin transfusion syndrome

Abstract: ObjectiveWe tested the hypothesis that increasing severity of chorioamnion membrane separation (CAS) after fetoscopic laser surgery (FLS) for twin‐twin transfusion syndrome (TTTS) is associated with worse pregnancy outcomes.MethodsProspective cohort of patients undergoing FLS for TTTS between 2011 and 2018. CAS was defined as separation of fetal membranes from the uterine wall on post‐operative ultrasound. Patient groups were defined: Group 1: No CAS; Group 2: CAS lower than 50th centile; Group 3: CAS upper th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 30 publications
3
21
0
Order By: Relevance
“…With respect to TTTS pregnancies, sensitivity analysis identified no significant change in the findings of this meta-analysis in terms of GA at intervention, interval from intervention to delivery, PPROM < 34 weeks of gestation, preterm delivery < 32 weeks of gestation and neonatal survival. However, after removing the studies by Papanna et al 6 , Ortiz et al 15 and Bergh et al 1 , GA at delivery was not significantly different between TTTS pregnancies and those not complicated by iCAS.…”
Section: Sensitivity Analysis and Publication Biasmentioning
confidence: 80%
See 3 more Smart Citations
“…With respect to TTTS pregnancies, sensitivity analysis identified no significant change in the findings of this meta-analysis in terms of GA at intervention, interval from intervention to delivery, PPROM < 34 weeks of gestation, preterm delivery < 32 weeks of gestation and neonatal survival. However, after removing the studies by Papanna et al 6 , Ortiz et al 15 and Bergh et al 1 , GA at delivery was not significantly different between TTTS pregnancies and those not complicated by iCAS.…”
Section: Sensitivity Analysis and Publication Biasmentioning
confidence: 80%
“…The pooled results of this systematic review and meta-analysis confirm that earlier GA at the time of intervention is associated with higher odds of iCAS. This finding could be attributed to increased risk of interference Ortiz (2016) 15 Takano (2018) 10 Total (95% CI) Heterogeneity: τ 2 = 0.68; χ 2 = 20.26, df = 4 (P = 0.0004); I 2 = 80% Test for overall effect: Z = 2.53 (P = 0.01) Ortiz (2016) 15 Takano (2018) 10 De Zoysa (2020) 8 Bergh (2020) 1 Total (95% CI) Heterogeneity: τ 2 = 2.46; χ 2 = 29.95, df = 5 (P < 0.0001); I 2 = 83% Test for overall effect: Z = -0.10 (-0.58 to 0.38) De Zoysa (2020) 8 Bergh (2020) 1…”
Section: Interpretation Of Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have tried to identify the risk factors that contribute to the occurrence of PPROM, mainly after the laser coagulation for TTTS, but conclusions remain inconsistent [1, 3, 7, 8, 27]. It has been reported that when the membrane trauma is complicated by chorioamniotic membrane separation [6, 28-31] or septostomy [5, 32, 33], the rates of PPROM are higher. CO shares several technical similarities with fetoscopic laser coagulation for TTTS; however, the risk factors for PPROM after CO have been poorly studied.…”
Section: Discussionmentioning
confidence: 99%